Prediction of Basic Wind Speed for Battambang Province - Chanthorn LIN; Rattana CHHIN; Virak HAN; Piseth DOUNG (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2022)
Basic wind speed is a very essential parameter used for conversion into wind loads on building structures. In Cambodia, the information of basic wind speed remains uncertain due to insufficient fundamental studies on the wind characteristics associated with regional climate. The aim of this paper is to predict the basic wind speed in Battambang, a northwest province of Cambodia using statistical and probabilistic approaches. The datasets have been collected from Mekong River Commission data portal in forms of hourly wind speed, and were then statically converted to 3-second gusts speed using Gaussian distribution transformation. The extreme value distributions such as Gumbel and Gringorten were used to analyze the extreme speed in accordance with a return period. The results showed that with a return period of 50 and 700 years, the basic wind speed was found to be 31.3 m/s, 41.1 m/s by Gumbel and 28.4 m/s, 36.1 m/s by Gringorten, respectively. These results provided a new look over traditionally uncertain basic wind speed selection and can be an alternative for estimation of wind loads for the design of building structures in Battambang.